COMPARISON OF SELECTED PROVISIONS - CIGARETTE MANUFACTURER LIABILITY LEGISLATION. (Tufts Archival Research Center, 2007)
Liability comparison of Illinois, Wisconsin, and Rhode Island. Offers selected definitions of smoking and cigarette producers. Lists elements required for the establishment of liability, defenses, proof, contributions, and damages.